Distributed power resources : operation and control of connecting to the grid - Li, Ruisheng (Academic Press, 2019)
Distributed Power Resources: Operation and Control of Connecting to the Grid presents research and development, lists relevant technologies, and draws on experience to tackle practical problems in the operation and control of distributed power. Key problems are identified and interrogated, as are requirements and application methods, associated power conversion tactics, operational control protections, and maintenance technologies. The title gives experimental verification of the technologies involved in several demonstration projects, including an active multi-resource distribution grid, and a high-density distributed resources connecting ac/dc hybrid power grid. The book considers the development of distributed photovoltaic power, wind power, and electric vehicle energy storage. It discusses the characteristics of distributed resources and the key requirements and core technologies for plug-and-play applications.